Konsistensi Perencanaan Strategis Sektor Pertanian pada Pemerintah Kabupaten Situbondo - Wahyudi, Tri (Jurnal Ilmiah Administrasi Publik, 2018)
This study aims to: (1) explain the consistency of agricultural sector strategic planning in Situbondo; (2) explain the role of each local actors in the effort to formulate a consistent agricultural strategic planning document. Based on data and data analysis, this research concludes that the consistency level of strategic planning document of agricultural sector in Situbondo Regency is very good but there are still 33,33% priority program in RPJMD/ Middle Range Work Plans which is not referenced by program of strategic planning document and there are 30% of activity in strategic planning document year 2017 not referenced by Renja/Annual Work Plans year 2017. Some important efforts that have been made by local government actors to produce a consistent Agricultural Strategic Planning document are: Synchronizing between RPJMD and Agricultural Strategic Planning document; Coordinating between BAPPEDA/Local Planning Department and Dinas TPHP/Food Crops, Horticulture and Plantation Department; Assessing the consistency of the Strategic Plan consisting of consistency on targets, programs and activities , performance indicators and activities and indicative strategic ceilings.